Adult congenital lobar emphysema in pregnancy - Critchley, P S; Forrester-Wood, C P; Ridley, P D (Thorax, 1995)
A young woman presented with left sided chest pain. Chest radiography revealed a hyperexpanded left upper lobe and the rare diagnosis of congenital lobar emphysema was made. She was then found to be pregnant. Thoracotomy and left upper lobectomy were performed during the pregnancy without adverse effects to the mother or fetus. The implications of pregnancy on the surgical management of this rare condition are discussed.